2018
DOI: 10.1093/brain/awy228
|View full text |Cite
|
Sign up to set email alerts
|

Induction of migraine-like headache, but not aura, by cilostazol in patients with migraine with aura

Abstract: Whether migraine headache and migraine aura share common pathophysiological mechanisms remains to be understood. Cilostazol causes cAMP accumulation and provokes migraine-like headache in migraine patients without aura. We investigated if cilostazol induces aura and migraine-like headache in patients with migraine with aura and alters peripheral endothelial function and levels of endothelial markers. In a randomized, double-blinded, placebo-controlled crossover study, 16 patients with migraine with aura (of wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
26
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 44 publications
0
26
0
Order By: Relevance
“…8 Migraine provocation using vasodilating drugs (glyceryl trinitrate, calcitonin-gene related peptide, and cilostazol) has been attempted in patients suffering from migraine with aura specifically. [40][41][42][43] Interestingly, in these studies, the drugs generally induced migraine attacks without aura, even in patients who previously experienced attacks with aura exclusively, while migraine attacks with aura were only rarely triggered. The present study is, to our knowledge, the first attempt of experimental migraine provocation, in migraine patients, using a vasoconstrictor drug.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…8 Migraine provocation using vasodilating drugs (glyceryl trinitrate, calcitonin-gene related peptide, and cilostazol) has been attempted in patients suffering from migraine with aura specifically. [40][41][42][43] Interestingly, in these studies, the drugs generally induced migraine attacks without aura, even in patients who previously experienced attacks with aura exclusively, while migraine attacks with aura were only rarely triggered. The present study is, to our knowledge, the first attempt of experimental migraine provocation, in migraine patients, using a vasoconstrictor drug.…”
Section: Discussionmentioning
confidence: 89%
“…Since there is a substantial pulmonary clearance of ET‐1, with a mean first‐pass clearance of approximately 50%, an explanation for this could be that a higher concentration of intravascular ET‐1 would reach the cerebral circulation in patients with a PFO. Another, more likely, explanation is based on the observation that microemboli, for example, in the form of air bubbles, entering the cerebral circulation can induce CSD in animals and that intravenous administration of agitated saline in migraine patients with PFO may occasionally induce migraine aura . Further, rare occurrences of suspected transient ischemic attacks and neuroimaging‐verified ischemic stroke following sclerotherapy have been reported almost exclusively in patients with right‐to‐left cardiac shunts, mostly PFOs .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies reported that cilostazol induced a migraine-like headache. Those reports suggested the mechanism of headache was due to accumulation of cyclic adenosine monophosphate (cAMP) in brain cells that induced by cilastazol [4][5][6]. The PDE III enzymes catalyzes the degradation of both cyclic adenosine monophosphate (cAMP) and cyclic guanosine monophosphate (cGMP).…”
mentioning
confidence: 99%